The Effect Internet to Learning English for Young Learner - Hasanah, Uswatun; Nasiyah, Sigit Ahmad Fauzan; Cahyani, Dita Indah; Sofia, Ana (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2024)
English helps learners provide themselves with knowledge and progress. The Internet is currently the most popular source of information to get the information you need. This can affect the progress of English-speaking children. The researcher's goal in preparing this article is to find the positive and negative effects of learning English for young learners via the Internet. The method used in this study is a case study by interviewing a subject analysis of 25 mothers with children attending Islamic Schools TK Khalifah, TK DWI ASIH 2, and TK CINTA BANGSA. In the interview, mothers are asked about the positive and negative effects of learning English for their children over the internet. As a result of the analysis,learning English to children via the Internet generally has positive and negative effects. This has the positive effect that children are more likely to follow what they hear and see on the Internet. As children pronounce English, they can develop creativity and children can develop an interestin learning English. In other words, the negative effects of learning English over the Internet develop semi-linguisticism in which children cannot master the language to the fullest, impair their psychological development, and children are not fluent in Indonesian. Children tend to like gadgets. As a result, researchers can find the negative and positive effects of learning English for young learners via the Internet.